(untitled) (Bangladesh Journal of Agricultural Research, 2023)
The experiment was conducted at the research field and post graduate laboratory of Plant Pathology Department, Hajee Mohammad Danesh Science and Technology University, Dinajpur, during 2015 - 2016 to find out the performance of different source’s seed potatoes and select suitable methods for improvement of farm saved seed potatoes. In the experiment, farm saved seed was compared with the certified seed, positive selection’s seed, seed plot technique’s (STP) seed Potato and Truthfully level seed potato as of BARI Alu-8(Cardinal). The maximum yield (27.72 t ha-1) was recorded from positive selection’s seed, which was similar to Certified and SPT seeds. The maximum plants of farmer’s seed potatoes (≥ 8 %, 7.33 % and 4.17 %) were infected by PVY, PLRV and PMV, respectively. The seed potatoes of positive selection and seed plot technique were the best alternatives to supplement the certified seed. Bangladesh J. Agril. Res. 46(3): 343-352, September 2021